Analysis of the Impact of Islamic Education Teacher Training on the Quality of Learning in Schools - Hijrotin, Dzaqi (Universitas Nurul Jadid, 2023)
This study aims to analyze the impact of Islamic Religious Education (PAI) teacher training on the quality of learning in schools. Using a mixed approach that combines quantitative and qualitative methods, this study explores how training affects teachers' pedagogical competence, motivation, and self-confidence, as well as their impact on learning processes and outcomes. Data were collected through questionnaires filled out by PAI teachers, in-depth interviews with principals and vice principals, and classroom observations. Quantitative analysis identified changes in teachers' perceptions of their competence and motivation, while qualitative analysis provided insights into training experiences and institutional support. The study findings indicate that PAI teacher training significantly improved teachers' pedagogical competence and motivation, which contributed to more effective teaching and more positive interactions with students. In addition, institutional support and consistent implementation of training outcomes also played an important role in the success of the training. This study provides recommendations for improving teacher training programs to make them more impactful and sustainable, and suggests the implementation of best practices in training to improve the quality of PAI learning in schools.